Rhetorical exercises in the Ukrainian language classes in the upper classes (Pedagogy of Higher and Secondary Education, 2012)
Pryadka YA. YU. Rhetorical exercises in the Ukrainian language classes in the upper classes.The article considers the existing methods of teaching the language classification exercises in rhetoric, that is directed on the development of the necessary rhetorical abilities and skills, based on them, the author offers the optimal system of exercises, which contributes to successful absorption of rhetorical knowledge of the language lessons.
Keywords: rhetoric; classification of exercises; rhetorical abilities and skills; preparatory; training; final exercises